IMPLEMENTATION OF INQUIRY METHODS IN INCREASING STUDENT ACTIVENESS AND LEARNING ACHIEVEMENT IN ISLAMIC RELIGIOUS EDUCATION (PAI) SUBJECTS AT NAHDLATUL ULAMA MIDDLE SCHOOL 'PACE. - Dian Mohammad Hakim; Winarto Winarto; Imam Khoirul Ulumuddin; Hamid Sakti Wibowo; Taufikur Rahman (Universitas Wahid Hasyim Semarang, 2022)
Islamic religious education is one of the most important subjects. As a strategy of planting and forming commendable morality. Considering the position of PAI is so important, learning should be carried out with the right method in order to create a conducive, active, creative and critical learning environment. Apart from the many learning methods that can be used by a teacher, the teacher as a learning resource as well as a deliverer of Islamic religious education must choose the accuracy of the method used in teaching. This study will focus on the Inquiry learning method. This research will find about: 1) Inquiry method learning planning, 2) Inquiry method learning implementation and 3) Assessment and learning outcomes of Inquiry method learning in increasing student activeness and learning achievement in PAI subjects at SMK NU Pace Nganjuk.This study used a qualitative approach and the type of research used was classroom action research (PTK). Researchers act as participants. Sources of data were obtained from the principal, PAI subject teachers, teacher councils, and students. Data collection procedures using the method of observation, interviews, and documentation. Data analysis by means of data reduction, data presentation, conclusion and data verification.Research Results: The conclusion from the results of this study is that implementing the inquiry method in Islamic Education subjects can increase the activeness and learning achievement of class XI accounting students of SMK NU Pace Nganjuk.